Cost-effectiveness of dengue vaccination in ten endemic countries. Issue 3 (8th January 2018) - Zeng, Wu; Halasa-Rappel, Yara A.; Baurin, Nicolas; Coudeville, Laurent; Shepard, Donald S.
Highlights: Routine vaccination at age 9 would avert 22–23% of dengue illness costs. Cost-effectiveness ratios averaged 4216/DALY in Latin America and 3751 in Asia. From a societal perspective, vaccination would be cost saving in 3 of the 10 sites. Vaccination would be cost effective or highly cost effective in all remaining sites. Abstract: Following publication of results from two phase-3 clinical trials in 10 countries or territories, endemic countries began licensing the first dengue vaccine in 2015. Using a published mathematical model, we evaluated the cost-effectiveness of dengue vaccination in populations similar to those at the trial sites in those same Latin American and Asian countries. Our main scenarios (30-year horizon, 80% coverage) entailed 3-dose routine vaccinations costing US20/dose beginning at age 9, potentially supplemented by catch-up programs of 4- or 8-year cohorts. We obtained illness costs per case, dengue mortality, vaccine wastage, and vaccine administration costs from the literature. We estimated that routine vaccination would reduce yearly direct and indirect illness cost per capita by 22% (from US10.51 to US8.17) in the Latin American countries and by 23% (from US5.78 to US4.44) in the Asian countries. Using a health system perspective, the incremental cost-effectiveness ratio (ICER) averaged US4, 216/disability-adjusted life year (DALY) averted in the five Latin American countries (range: US666/DALY in Puerto Rico to US5, 865/DALY in Mexico). In the five Asian countries, the ICER averaged US3, 751/DALY (range: US1, 935/DALY in Malaysia to US5, 101/DALY in the Philippines). From a health system perspective, the vaccine proved to be highly cost effective (ICER under one times the per capita GDP) in seven countries and cost effective (ICER 1–3 times the per capita GDP) in the remaining three countries. From a societal perspective, routine vaccination proved cost-saving in three countries. Including catch-up campaigns gave similar ICERs. Thus, this vaccine could have a favorable economic value in sites similar to those in the trials.